Nikah Sirri: Keabsahan Dan Akibatnya - Maria Lailia Rahman (LPPM Institut Agama Islam Al-Hikmah Tuban, 2018)
Abstract: Marriage is a very important institution in society. The existence of this institution is to legalize the legal relationship between a man with a woman. Because of the importance of marriage in a State, required registration of marriages. In Indonesia has set the legal registration of marriages. With the recording obtained legality of marriage. Recording weddings will also protect the rule of law, as well as keeping the benefit of the community. While marriage Sirri is listed on the marriage without the legal institutions, the problems of marriage Sirri still a lot going on in the community. The impact becomes a complex problem in society, so it is still important to be studied. This paper will discuss the Sirri marriage between validity and consequences.